Probing renal blood volume with magnetic resonance imaging. (17th January 2020) - Niendorf, Thoralf; Seeliger, Erdmann; Cantow, Kathleen; Flemming, Bert; Waiczies, Sonia; Pohlmann, Andreas
Abstract: Damage to the kidney substantially reduces life expectancy. Renal tissue hypoperfusion and hypoxia are key elements in the pathophysiology of acute kidney injury and its progression to chronic kidney disease. In vivo assessment of renal haemodynamics and tissue oxygenation remains a challenge. Blood oxygenation level–dependent (BOLD) magnetic resonance imaging (MRI) is sensitive to changes in the effective transversal relaxation time (T2 *) in vivo, and is non‐invasive and indicative of renal tissue oxygenation. However, the renal T2 * to tissue pO2 relationship is not governed exclusively by renal blood oxygenation, but is affected by physiological confounders with alterations in renal blood volume fraction (BVf) being of particular relevance. To decipher this interference probing renal BVf is essential for the pursuit of renal MR oximetry. Superparamagnetic iron oxide nanoparticle (USPIO) preparations can be used as MRI visible blood pool markers for detailing alterations in BVf. This review promotes the opportunities of MRI‐based assessment of renal BVf. Following an outline on the specifics of renal oxygenation and perfusion, changes in renal BVf upon interventions and their potential impact on renal T2 * are discussed. We also describe the basic principles of renal BVf assessment using ferumoxytol‐enhanced MRI in the equilibrium concentration regimen. We demonstrate that ferumoxytol does not alter control of renal haemodynamics and oxygenation. Preclinical applications of ferumoxytol enhanced renal MRI as well as considerations for its clinical implementation for examining renal BVf changes are provided alongside practical considerations. Finally, we explore the future directions of MRI‐based assessment of renal BVf.